The Effect Of Casgot Fertilizer On The Growth Of Cucumber Plants - Fakhrur Roji Ritonga, Muhammad; Walida, Hilwa; Elizabeth Mustamu, Novilda; Ayu Putri Septyani, Ika (International Journal of Science, Technology & Management, 2024)
Regular use of organic fertilizer can improve soil health, reduce erosion, and increase agricultural sustainability by reducing dependence on synthetic chemicals. Kasgot fertilizer or used maggot fertilizer is a type of organic fertilizer produced from maggot droppings (larva lalat Black Soldier Fly) after they decompose organic waste. This fertilizer is rich in essential nutrients such as nitrogen, phosphorus and potassium, and contains various beneficial microorganisms that help increase soil fertility. This research aims to determine the effect of cassava fertilizer on the growth of cucumber plants (Cucumis sativus L.).This study used non-factorial RAK with 4 administration dose levels, namely: M0= 0 grams/planting hole, M1= 5 grams/planting hole, M2= 10 grams/planting hole and M3= 20 grams/planting hole. Data were analyzed using analysis of variance tests on the parameters of plant height, number of leaves and root weight. The results of the research showed that the parameters of plant height and number of leaves showed significant differences between plants aged 2 WAP and 4 WAP, while root weight did not have a significant difference between treatments and each replication. Additional doses or other organic materials are needed to increase the macro nutrients available in the soil.